2014
DOI: 10.1371/journal.pone.0102472
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Water Flow Stimulation to the Lower Limbs Modulates Excitability of Primary Motor Cortical Regions Innervating the Hands: A Transcranial Magnetic Stimulation Study

Abstract: Whole-body water immersion (WI) has been reported to change sensorimotor integration. However, primary motor cortical excitability is not affected by low-intensity afferent input. Here we explored the effects of whole-body WI and water flow stimulation (WF) on corticospinal excitability and intracortical circuits. Eight healthy subjects participated in this study. We measured the amplitude of motor-evoked potentials (MEPs) produced by single transcranial magnetic stimulation (TMS) pulses and examined condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Priming the activity of specific interneurons synapsing in M1 was found to alter the neural plasticity without modifying M1 excitability [43,44], thus supporting the notion that heterosynaptic plasticity may account for the effects of priming. Experiments 2 and 3 indicated that WI did not alter corticospinal excitability or intracortical excitability, consistent with previous studies [39,45]. In contrast, the cholinergic activity, as evaluated by SAI, significantly increased for at least 8.5 min after WI and returned to baseline at 21.5 min post-WI.…”
Section: Discussionsupporting
confidence: 88%
“…Priming the activity of specific interneurons synapsing in M1 was found to alter the neural plasticity without modifying M1 excitability [43,44], thus supporting the notion that heterosynaptic plasticity may account for the effects of priming. Experiments 2 and 3 indicated that WI did not alter corticospinal excitability or intracortical excitability, consistent with previous studies [39,45]. In contrast, the cholinergic activity, as evaluated by SAI, significantly increased for at least 8.5 min after WI and returned to baseline at 21.5 min post-WI.…”
Section: Discussionsupporting
confidence: 88%
“… 20 , 43 , 54 Increase in M1 excitability was also reported in response to large-area non-noxious somatosensory stimuli. This was demonstrated by reduced motor activity threshold, increased amplitude of motor-evoked potentials, and increased intracortical facilitation in response to whole-hand or whole-body water flow stimulation 60 , 61 and in response to whole-hand mesh-flow electrical stimulation. 23 , 24 Thus, the theoretical increase in M1 excitability in large-body compression can be attributed to CIA in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the performance improvement seen after HWI could be attributed to the increase in muscle temperature through heat conduction and by peripheral vasodilation, contributing to faster restoration of energy stores and acceleration of the rate of cross-bridge disconnection (Stienen et al 1996;He et al 2000). Although con rmed only when associated with water movement at thermoneutral temperatures (Sato et al 2014;Sato et al 2015), stimulation of peripheral thermoreceptors during immersions at 40°C could contribute to increased performance by virtue of increased corticospinal excitability, decreased intracortical inhibition and increased intracortical facilitation (Sato et al 2015). All these factors could explain the increase in muscle contraction speed.…”
Section: Anaerobic Mechanical Performance After Cold and Hot Water Im...mentioning
confidence: 99%